Soldier repatriation popular and political responses - Dahl-Martinsen, Kare (Ashgate Pub., 2013)
Britain, Denmark and Germany all deployed soldiers soon after the 9/11 attacks, yet their role in Afghanistan and the casualty rates suffered, have been vastly different. This book looks at how their casualties influenced the framing of the war by analysing the political discourse about the casualties.